Third contribution to the knowledge of water mites from the Comoros, with the description of two new species (Acari: Hydrachnidia) - Pešić, Vladimir; Smit, Harry; Mary, Nathalie (Zootaxa, 2015)
New records of water mites (Acari: Hydrachnidia) from the Comoros are presented. Two species new to science, Torrenticola comorosensis (Torrenticolidae) and Sterkspruitia comorosensis (Hygrobatidae) are described; the latter species is the second known species of the genus Sterkspruitia Cook, 2003. First records are given for Limnochares crinita Koenike, 1898 and Mamersella thienemanni K. Viets, 1929. Additional measurements, figures and information on the morphology are given for specimens assigned to the Monatractides ventriosus—species complex.